Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Perusahaan Perbankan yang Terdaftar di BEI Tahun 2020-2022 - Naily, Farida Chusnia Naily; Hudzafidah, Khusnik; Widayanto, Mutinda Teguh (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2024)
The purpose of this research is to determine the financial ratio of profit growth in banking companies listed on the Indonesia Stock Exchange in 2020-2022. This research has 22 banks as samples. The sampling technique used in this research is a non-probability sampling technique using a purposive sampling technique. Testing was carried out using the Statistical Package For Social Science (SPSS) 26 application, which consists of classical assumption tests, multiple regression analysis, coefficient of determination and hypothesis testing. The research results show that: 1) Current Ratio has a partially significant effect on the Profit Growth variable; 2) Debt to Equity Ratio does not have a partially significant effect on the Profit Growth variable; 3) Average Collection Period does not have a partially significant effect on the Profit Growth variable; 4) Net Profit Margin has a partially significant effect on the Profit Growth variable; 5) Price Earning Ratio has a partially significant effect on the Profit Growth variable. Keyword: Financial Ratios and Profit Growth